ROLE-PLAYING GAMES IN GERMAN LANGUAGE LESSONS AS AN EFFECTIVE TEACHING METHOD - Sayora Abduraimovna Akhmedova (International Journal of Literature and Language Studies, 2026)
This article examines the role of role-playing games in teaching German. It analyzes the main advantages of this method and its impact on the development of students' communicative competence. Examples of the use of role-playing games at various stages of learning are provided. It is noted that the use of role-playing games helps increase student motivation, develop verbal skills, and foster intercultural competence.